A novel mouse model for inhibition of DOHH-mediated hypusine modification reveals a crucial function in embryonic development, proliferation and oncogenic transformation - Henning Sievert; Nora Pällmann; Katharine K. Miller; Irm Hermans-Borgmeyer; Simone Venz; Ataman Sendoel; Michael Preukschas; Michaela Schweizer; Steffen Boettcher; P. Christoph Janiesch; Thomas Streichert; Reinhard Walther; et al. (The Company of Biologists, 2014)
The central importance of translational control by post-translational modification has spurred major interest in regulatory pathways that control translation. One such pathway uniquely adds hypusine to eukaryotic initiation factor 5A (eIF5A), and thereby affects protein synthesis and, subsequently, cellular proliferation through an unknown mechanism. Using a novel conditional knockout mouse model and a Caenorhabditis elegans knockout model, we found an evolutionarily conserved role for the DOHH-mediated second step of hypusine synthesis in early embryonic development. At the cellular level, we observed reduced proliferation and induction of senescence in 3T3 Dohh−/− cells as well as reduced capability for malignant transformation. Furthermore, mass spectrometry showed that deletion of DOHH results in an unexpected complete loss of hypusine modification. Our results provide new biological insight into the physiological roles of the second step of the hypusination of eIF5A. Moreover, the conditional mouse model presented here provides a powerful tool for manipulating hypusine modification in a temporal and spatial manner, to analyse both how this unique modification normally functions in vivo as well as how it contributes to different pathological conditions.